Richard H. Tourin papers - Tourin, Richard H.
Correspondence, Tourin's unpublished memoir, and other papers relating to the American communist movement; New York City's Jewish immigrant community of the 1930s and 1940s; Philip Rosenbliet, Tourin's uncle and director of a Soviet spy ring; and children's schools and summer camps with leftist political connections such as Wo-Chi-Ca. Includes correspondence with Gene Gordon and June Levine.
Industrial physicist.
Collection material in English.
Keywords: Gordon, Gene -- Correspondence; Levine, June -- Correspondence; Rosenbliet, Philip; Camps -- United States; Communism -- United States; Communism in education; Education -- United States; Espionage, Soviet -- United States; Jews -- New York (State) -- New York; Socialism and youth -- United States; Spies -- United States; Subversive activities -- United States; Soviet Union -- Foreign relations -- United States; United States -- Foreign relations -- Soviet Union; Industrial physicists